KARAKTERISASI STRUKTUR LIPID DARI SPONS XESTOSPONGIA TESTUDINARIA - Ardyansyah Ibraham; Rudiyansyah Rudiyansyah; Andi Hairil Alimuddin (Tanjungpura University, 2021)
The aim of this study is to isolate and characterize the structure of metabolite compounds of the sponge Xestospongia testudinaria, which grows in West Kalimantan. 3000 grams of sponges were analyzed through a preparation and extraction process, which produced a methanol-dissolved extract with a mass of 77.2 grams. The methanol-dissolved extract of was parted using n-hexane and dichloromethane as solvents. Based on the results of phytochemical testing, it can be concluded that the dissolved fraction of dichloromethane contains alkaloids and terpenoids or steroids. The purification process was carried out on 2.4 grams of dichloromethane-dissolved fraction by means of vacuum liquid chromatography, and ten separation fractions were obtained with eluated ethyl acetate : n-hexane as eluent. The separation fractions of FD 3, FD 4, FD 5 and FD 6, which have the same chromatogram characteristics were combined to be purified by means of preparative chromatography. The preparative process was carried out with chloroform : methanol 98:2 eluent, and three chromatogram isolates were produced. The chromatogram isolates with Rf = 0.44 and a mass of 8 milligrams were analyzed by FTIR spectroscopy using pellet KBr and 1H-NMR spectroscopy using CD3OD solvent. Based on the results of data analysis, it is concluded that the predicted content of metabolite compound of the Xestospongia testudinaria sponge sample growing in West Kalimantan waters is propyl-6,7,8-trihydroxy-4-pentadecenoate compound, which is a compound of the fat or lipid ester group with a typical IR absorption peak of the C = O group and C – O at wave numbers 1735.93 – 1766.80 cm-1 and 1111.00 – 1315.45 cm-1 and the containing 11 environments of hydrogen atoms scattered in the 1H-NMR chemical shift from 0.85 ppm to 3.97 ppm.